Nowe technologie na lekcjach języka polskiego - Handzel, Agnieszka (Postscriptum Polonistyczne, 2020)
The article discusses changes in education that have resulted from the digital revolution. The author analyses changes in young people’s behaviour, their mentality, their methods of learning and the consequences of these changes. She describes the situation of young people and teachers being forced to change their way of thinking and modernize the modes of cooperation at school. She presents some possibilities of using multimedia tools in Polonistic didactics. They can help in the effective shaping of skills needed to function properly in the future.